Evidence of airborne excretion of Pneumocystis carinii during infection in immunocompetent rats. Lung involvement and antibody response. - Jean Menotti (Public Library of Science (PLoS), 2013)
To better understand the role of immunocompetent hosts in the diffusion of Pneumocystis in the environment, airborne shedding of Pneumocystis carinii in the surrounding air of experimentally infected Sprague Dawley rats was quantified by means of a real-time PCR assay, in parallel with the kinetics of P. carinii loads in lungs and specific serum antibody titres. Pneumocystis-free Sprague Dawley rats were intratracheally inoculated at day 0 (d0) and then followed for 60 days. P. carinii DNA was detected in lungs until d29 in two separate experiments and thereafter remained undetectable. A transient air excretion of Pneumocystis DNA was observed between d14 and d22 in the first experiment and between d9 and d19 in the second experiment; it was related to the peak of infection in lungs. IgM and IgG anti-P. carinii antibody increase preceded clearance of P. carinii in the lungs and cessation of airborne excretion. In rats receiving a second challenge 3 months after the first inoculation, Pneumocystis was only detected at a low level in the lungs of 2 of 3 rats at d2 post challenge and was never detected in air samples. Anti-Pneumocystis antibody determinations showed a typical secondary IgG antibody response. This study provides the first direct evidence that immunocompetent hosts can excrete Pneumocystis following a primary acquired infection. Lung infection was apparently controlled by the immune response since fungal burdens decreased to become undetectable as specific antibodies reached high titres in serum. This immune response was apparently protective against reinfection 3 months later.